Shared and Unique Features Distinguishing Follicular T Helper and Regulatory Cells of Peripheral Lymph Node and Peyer’s Patches - Georgiev, Hristo; Ravens, Inga; Papadogianni, Georgia; Halle, Stephan; Malissen, Bernard; Loots, Gabriela G.; Förster, Reinhold; Bernhardt, Günter (Frontiers in Immunology, 2018)
Follicular helper (TFH) and regulatory (TFR) cells are critical players in managing germinal center (GC) reactions that accomplish effective humoral immune responses. Transcriptome analyses were done comparing gene regulation of TFH and TFR cells isolated from Peyer’s Patches (PP) and immunized peripheral lymph nodes (pLN) revealing many regulatory patterns common to all follicular cells. However, in contrast to TFH cells, the kinetic but also the extent of regulation regarding many genes was attenuated in pLN TFR cells when compared to those of PP. Additionally, PP but not pLN TFR cells were largely unresponsive to IL2 and expressed Il4 as well as Il21. Together with fundamental differences in gene expression that were found between cells of both compartments this emphasizes specific adaptations of follicular T cell functions to their micro-milieu. Moreover, although GL7 expression distinguishes matured follicular T cells, GL7+ as well as GL7- cells are present in the GC.